MELATONIN EFFICIENCY IN MULTIPLE TREATMENT OF ABNORMAL UTERUS BLEEDING - E. N. Tananakina (IRBIS LLC, 2016)
Objective. To increase efficiency and to develop pathogenetically substantiated treatment regimen of abnormal uterine bleeding. Materials and Methods. Analysis of 96 cases of abnormal uterine bleeding among women of reproductive age with combined extragenital pathology. On the background of a standard survey further determination of hormones in the blood (cortisol), the expression of anxiety on the Hamilton Anxiety Scale. On the background of the standard hemostatic therapy in a hospital environment 48 women (group I) were additionally prescribed melatonin, 48 women (group II) were prescriebed standard treatment. Control group III - 23 healthy women. Results. The use of the drug melatonin (3 mg №2) in the treatment of abnormal uterine bleeding among women of reproductive age with combined extragenital pathology promotes considerable reduction of anxiety and the growth of cortisol level, which accelerates the formation of the adaptation syndrome, thereby increasing the effectiveness of the treatment.